What proportion of congenital abnormalities can be prevented?. Issue 6876 (20th February 1993) - Czeizel, A E; Intôdy, Z; Modell, B
Abstract : OBJECTIVE--To estimate the proportion of preventable congenital abnormalities in Hungary. DESIGN--Analysis of available Hungarian data-bases and of the effectiveness of primary, secondary, and tertiary preventive methods. SETTING--Databases of ad hoc epidemiological studies and of the Hungarian congenital abnormality registry. MAIN OUTCOME MEASURES--Prevalence at birth and prevalence after prevention in 73 congenital abnormality types or groups. RESULTS--Preventive methods are available for 51 (70%) of the 73 congenital abnormality types or groups evaluated. The birth prevalence of all congenital abnormalities could be reduced from 65 to 26 per 1000; thus 39 per 1000 (60%) are preventable. Without congenital dislocation of the hip, which is unusually common in Hungary, the preventable proportion of congenital abnormalities is 52%. CONCLUSION--Many congenital abnormalities can be prevented, but as they do not represent a single pathological category there is no single strategy for their prevention.